ANALISIS HUMAN CAPITAL DALAM MENINGKATKAN ETOS KERJA PEGAWAI SATUAN POLISI PAMONG PRAJA DAN PEMADAM KEBAKARAN KABUPATEN BOLAANG MONGONDOW SELATAN - Yakup, Yakup; Hasanuddin, Hasanuddin; Usu, Idrus; Ishak, Olfin; Gobel, Dedi (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to analyze the role of human capital in improving the work ethic of employees in the Civil Service Police Unit (Satpol PP) and Fire Department (Damkar) in Bolaang Mongondow Selatan Regency. This research employs a mixed-methods approach, incorporating both qualitative and quantitative methods. The qualitative method is used to gain an in-depth understanding of the factors influencing human capital and work ethic, while the quantitative method is applied through path analysis to examine the causal relationships between research variables. The study's sample consists of 78 employees of Satpol PP and Damkar, selected using a total sampling method. The findings reveal that each dimension of human capital has a significant impact on employees' work ethic. Knowledge plays a role in enhancing professionalism and dedication to work. Higher expertise encourages discipline and responsibility in performing duties. An individual's ability to complete tasks positively correlates with a stronger work ethic. Additionally, technical and interpersonal skills are key factors in fostering a productive and collaborative work culture. Collectively, these four dimensions of human capital significantly contribute to improving employees' work ethic. These findings emphasize that investment in human resource development—through training, education, and work experience—is an effective strategy for cultivating a strong and professional work ethic. Therefore, government institutions, particularly Satpol PP and Damkar, should adopt policies that support human capital development to enhance the effectiveness and quality of public services.